Resources of modernization of the local social infrastructure in the Russian Federation - E V Frolova (RUDN journal of Sociology, 2014)
Social infrastructure is the foundation for the development of municipality meeting basic needs and interests of population, creating conditions for its subsistence and reproduction. Thus, the study of the conditions and factors of modernization of social infrastructure and the basic problems of its development in contemporary Russia acquires particular relevance. The author evaluates the development of social infrastructure on the basis of the expert survey results (officials and elected representatives of local self-government of the Russian Federation were interviewed) and suggests some ways to support the local authorities in order to modernize the social infrastructure of municipalities.